STUDENTS’ LEARNING STRATEGIES ON MICROTEACHING COURSE : A CASE STUDY IN WEST SUMATERA UNIVERSITIES - Khairinnisa; Melvina, Edwar Kemal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine students' speaking learning strategies in microteaching courses, particularly in English language education at PGRI University of West Sumatra. This study uses a qualitative approach with a narrative inquiry method. The research subjects are a number of students who have completed the microteaching course in the 6th semester of 2024. The research instruments used are structured interviews, participant observation, and documentation. Metacognitive strategies appear to be the most dominant, as most students emphasize planning before acting, monitoring themselves while speaking, and conducting self-evaluation afterwards. Cognitive strategies are also widely used, mainly through translation, note-taking, and the use of social media or digital applications to enrich vocabulary and strengthen grammar knowledge. Meanwhile, social-affective strategies helped students reduce anxiety, maintain confidence, and ensure language accuracy by seeking clarification from lecturers, classmates, or applications. These findings indicate that the three strategies complement each other, with metacognitive strategies as the main foundation, cognitive strategies as language support tools, and social-affective strategies as confidence-building factors in microteaching.